Desempenho reprodutivo e diferenciação gonadal em piau-três-pintas, Leporinus friderici, Bloch 1794 - Souza, Thiago Gonçalves de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The objectives of this study were to evaluate the reproductive performance and gonadal differentiation process Leporinus friderici. First we assess the evolution of the meiotic process and the reproductive performance of L. friderici broodstock induced with conventional and lower dose of crude carp pituitary extract (EC) and mammalian gonadotropin releasing hormone analogue associated with metoclopramide (mGnRHa + MET ). Subsequently, we investigated the beginning and the characteristics of gonadal differentiation process of this species exposed at 25 and 29°C. For the evaluation of reproductive performance, we used the EC at doses of 0.5 and 5.5 mg / kg (conventional dose) and at doses of 0.5 and 1.0mg / kg (lower doses). Parallel use of a single dose of 40pg + 20mg mGnRHa MET / kg (conventional dose) and two doses of 4pg + 2mg; and 4pg + 8mg of mGnRHa + MET / kg (lower doses). For evaluation of gonadal differentiation process were randomly sampled five fish 50, 70, 90, 110, 130, 150, 170, 190, 210 and 240 days after hatching (DAE), exposed to 25 and 29°C in recirculation system water. We conclude that viable L. friderici embryos can be obtained with low doses of EC, but not with standard doses. Could not get viable embryos L. friderici with use of mGnRHa + MET, at least with the doses and procedures used here, as these caused low fertility, low hatching and reduced egg quality. With respect to gonadal differentiation process, we have demonstrated that the higher temperature (29°C) caused an increase in average weight (P) and standard length (CP), intensified gonadal differentiation and provided a greater number of females L. friderici. In conclusion, it is possible that the species has any toxicity caused by excess GnRH, luteinizing hormone or the gonadal steroids, which would be transmitted to the female embryos before the ovulation process, killing them. With the production of females, which is the genre of greater economic ...

Os objetivos deste trabalho foram avaliar o desempenho reprodutivo e o processo de diferenciação gonadal do Leporinus friderici. Primeiramente avaliamos a evolução do processo meiótico e o desempenho reprodutivo de matrizes de L. friderici induzidas com doses convencionais e reduzidas de extrato bruto de hipófise de carpa (EC) e de hormônio liberador de gonadotropinas análogo ao de mamífero associado à metoclopramida (mGnRHa + MET). Posteriormente, investigamos o início e as características do processo de diferenciação gonadal desta espécie expostos a 25 e 29°C. Para a avaliação do desempenho reprodutivo, utilizamos o EC em doses de 0,5 e 5,5mg/Kg (doses convencionais) e em doses de 0,5 e 1,0mg/Kg (doses reduzidas). Paralelamente utilizamos dose única de 40pg de mGnRHa + 20mg de MET/Kg (dose convencional) e duas doses de 4pg + 2mg; e 8pg + 4mg, de mGnRHa + MET/Kg (doses reduzidas). Para avaliação do processo de diferenciação gonadal foram amostrados aleatoriamente cinco peixes com 50, 70, 90, 110, 130, 150, 170, 190, 210 e 240 dias após eclosão (DAE), expostos a 25 e 29°C, em sistema de recirculação de água. Concluimos que embriões viáveis de L. friderici podem ser obtidos com doses reduzidas de EC, mas não com doses convencionais. Não foi possível obter embriões viáveis de L. friderici com uso de mGnRHa + MET, pelo menos com as doses e procedimentos aqui empregados, pois estes causaram baixa fertilidade, baixa eclosão e redução da qualidade dos ovos. Com relação ao processo de diferenciação gonadal, demonstramos que a temperatura mais elevada (29°C) provocou aumento no comprimento padrão (CP) e peso médio (P), intensificou a diferenciação gonadal e propiciou um maior número de fêmeas de L. friderici. Concluindo, é possível que a espécie apresente alguma toxicidade provocada pelo excesso de GnRH, hormônio luteinizante ou aos esteroides gonadais, os quais seriam transmitidos da fêmea para...
Keywords: Peixe - Reprodução; Temperatura; Femea; Desempenho; Gonadas; Fishes Reproduction